The Students Ability to Change the Health Interview Text become a Narrative at Seventh Grade of SMP IT Nurul Yaqin - Abdul Rahman Hatsama; Budi Riono; Budi Santoso (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study aims to describe students' ability in writing, especially developing narrative essays based on interview texts. The method used in this research is descriptive quantitative method. This research technique is carried out by giving the task of composing a narrative based on the interview text that has been provided to students. The instrument used is a test of the ability to change the text of a health interview into a narrative that is given to students in the form of a written test. The object of this research is students' essays which are assessed from the linguistic aspect including the ability to use spelling, diction, paragraphs, and the suitability of the narrative content with the interview text. The source of the data for this study were the seventh-grade students of SMP IT Nurul Yaqin, Sorong Regency, totaling 46 students from the number of 50 students in class VII. Collecting data in this study through test techniques. To analyse the data using the average formula. Based on the results of the study, it can be concluded that the seventh-grade students of SMP IT Nurul Yaqin, Sorong Regency are able to change the health interview text into a narrative. That is, as many as 61% can convert health interview texts into narratives, while 39% have not been able to convert health interview texts into narratives. This is based on the average value of 60, which is in the range of values ​​of 60-74 with sufficient category.